Study on structural modification of bentonite for oily water treatment in the oil and gas industry - Vu An; Phan Trong Hieu; Hoang Mai Chi; Nguyen Tuan Anh (Petrovietnam Journal, 2014)
The present study deals with the removal of oil from wastewater by organoclay in offshore processing platforms. The organoclay was prepared by combination of Binh Thuan bentonite with quaternary amine (hexadecyltrimethylammonium bromide). The wastewater samples were obtained from the preparation of artificial oily water in the Vietnam Petroleum Institute’s laboratory, with the initial oil concentration of wastewater within a maximum range of 230-1510 mg/l.XRD, TGA, and FTIR diagram of the prepared organoclay showed a considerable difference from those for natural bentonite which indicates the exchange of quaternary amine with Na+, K+ ions at the surface of bentonite. The concentration of oil in the wastewater samples decreased below 10 mg/l after treatment with organoclay. The results of processing wastewater with different oil concentrations showed that the optimal conditions for preparing organoclays are as followed: percentage of amine/bentonite: 15%, temperature: 40o C, time: 5h and pH: 4. On the evaluation of treating standard oily water samples, the same degree of oil decreasing ability was observed with the prepared bentonite and a commercial chemical (CETCO RM-10).